Effects of Appearance- and Performance-Enhancing Drugs on Personality Traits - Zaami, Simona; Minutillo, Adele; Sirignano, Ascanio; Marinelli, Enrico (Frontiers in Psychiatry, 2021)
Appearance and Performance Enhancing Drugs (APEDs) are commonly used by adolescents and young adults in an effort to improve not only athletic performance, but also physical and mental efficiency and sexual appearance. The rationale for using these drugs is grounded in the perceived importance of external appearance, the quest for health and youth, and the urge to boost one’s sexual performances. Although APED users tend to be quite moderate overall, some specific subpopulations can display a pathological use associated with high-risk behaviours. A wide and diverse range of APEDs is now easily accessible to almost anyone through backdoor online avenues. Common APEDs include anabolic–androgenic steroids, non-steroidal anabolics, anorectics, diuretics and ergo/thermogenics, nootropics, or "cognition enhancers", licit and illicit psychostimulants and finally, sexual enhancers. The use of APEDs appears linked to several psychopathological disorders of unclear prevalence, eg. body image disorders and eating disorders, perfectionism, but also depression and loneliness. The role of personality traits related to APED use has been investigated in adolescents and young adults, in elite and amateur athletes and in chemsexers and associated with the above reported personality traits. The studies herein analysed show that APEDs consumption in the general population is quickly growing into a public health concern. It is therefore essential to launch prevention and intervention projects aimed at promoting safe instrumental use of the body, not only in sports disciplines but also among the general population, in addition to psychological aid for people with substance use issues, depression and anxiety and body image disorders.